Changing Practices, Changing Education - Kemmis, Stephen. author. aut Link
XV, 278 p. 10 illus.
Keywords: This book aims to help teachers and those who support them to re-imagine the work of teaching, learning and leading. In particular, it shows how transformations of educational practice depend on complementary transformations in classroom-school- and system-level organisational cultures, resourcing and politics. It argues that transforming education requires more than professional development to transform teachers; it also calls for fundamental changes in learning and leading practices, which in turn means reshaping organisations that support teachers and teaching – organisational cultures, the resources organisations provide and distribute, and the relationships that connect people with one another in organisations. The book is based on findings from research conducted by the authors – the research team for the (2010-2012) Australian Research Council-funded Discovery Project Leading and Learning: Developing Ecologies of Educational Practice. The book provides an introduction to new contributions to practice theory: the theory of practice architectures (what practices are composed of) and the theory of ecologies of practices (how practices relate to one another). Among other examples of practices of learning, teaching, professional learning, leading and researching, the book provides a detailed analysis of a classroom lesson to demonstrate how the theories can be used in the analysis and interpretation of empirical material: practices and the conditions that form and are formed by them. .